ChemInform Abstract: Synthesis of Fluorine‐Containing Exoalkylidene β‐Lactams. Issue 23 (May 2016) - Nasr El Dine, Assaad; Gree, Danielle; Roisnel, Thierry; Caytan, Elsa; Hachem, Ali; Gree, Rene
Abstract: Propargylic gem‐difluorides are applied to the Kinugasa reaction affording novel exoalkylidene β‐lactams with a fluorine in the vinylic position.